An E-Training Model for Improving Early Childhood Teacher Competence in Purwakarta, Karawang, Subang, and Bekasi - Nurul Fahimah (UIN Sunan Gunung Djati Bandung, 2026)
In 2019–2020, Indonesia had 203,488 early childhood education (PAUD) units serving 5,691,201 students with 431,215 educators; West Java alone had 28,723 units. To address cost and distance barriers to competency development, this R&D study developed and tested an online training model (synchronous/asynchronous, MOOC-based) for PAUD educators. Data (interviews, observations, documentation, focus group discussions, questionnaires) from 70 sample participants indicated that educators possessed pedagogical, personality, social, and professional competencies but required continuous skill enhancement. Pre-post tests demonstrated significant competency improvement after the online training, and user trials reported high satisfaction and alignment with career needs. The study concluded that online training is effective when implemented collaboratively, participatory, and constructively to encourage educators' learning independence.